In Favor of Establishment: Regulation of Chromatid Cohesion in Plants - Bolaños-Villegas, Pablo; De, Kuntal; Pradillo, Mónica; Liu, Desheng; Makaroff, Christopher A. (Frontiers in Plant Science, 2017)
In eukaryotic organisms, the correct regulation of sister chromatid cohesion, whereby sister chromatids are paired and held together, is essential for accurate segregation of the sister chromatids and homologous chromosomes into daughter cells during mitosis and meiosis, respectively. Sister chromatid cohesion requires a cohesin complex comprised of structural maintenance of chromosome (SMC) adenosine triphosphatases and accessory proteins that regulate the association of the complex with chromosomes or that are involved in the establishment or release of cohesion. The cohesin complex also plays important roles in the repair of double-strand DNA breaks, regulation of gene expression and chromosome condensation. In this review, we summarize progress in understanding cohesion dynamics in plants, with the aim of uncovering differences at specific stages. We also highlight dissimilarities between plants and other eukaryotes with respect to the key players involved in the achievement of cohesion, pointing out areas that require further study.